Vascular Remodeling And Endothelial Dysfunction After Experimental Splenectomy - Azimova Masuda Karimovna, PhD (Genius Journals, 2026)
To investigate morphofunctional changes in blood vessels after splenectomy in an experimental model. Materials and Methods: The experiment was conducted on adult white male rats divided into a control group and two experimental groups examined on days 14 and 30 after splenectomy. Histological and morphometric methods were applied to assess endothelial integrity, vascular wall structure, and microcirculatory parameters. Results: Splenectomy resulted in endothelial dysfunction, arterial wall remodeling, and significant microcirculatory disturbances. Early changes were predominantly compensatory-adaptive, whereas later stages were characterized by persistent structural alterations, capillary rarefaction, and signs of chronic tissue hypoxia.
Keywords: splenectomy; endothelium; vascular remodeling; microcirculation